Pregled vrednotenj naravoslovnega znanja v prvem vzgojno-izobraževalnem obdobju osnovne šole - Kožuh, Vasja (Revija za elementarno izobraževanje, 2021)
This paper presents an overview of Slovenian elementary school evaluation of students' natural science knowledge in the first three years of elementary school. Science knowledge in Slovenia is not measured regularly; therefore, we have focused primarily on the results of the international TIMSS survey, which measures the mathematical and natural science knowledge of students. The TIMMS survey is performed every four years in various countries, and Slovenia participated from 1995 to 2015. After reviewing and analysing the results of the natural science examinations of Slovenian fourth-graders, we found a steady increase compared to the international average. However, at the same time, the positive attitude towards science lags behind.
Keywords: elementary school students; international TIMSS survey; knowledge evaluation; mednarodna raziskava TIMSS; naravoslovje; natural sciences; osnovnošolci; vrednotenje znanja